2005
DOI: 10.1038/sj.mp.4001663
|View full text |Cite
|
Sign up to set email alerts
|

Population-based and family-based studies on the serotonin transporter gene polymorphisms and bipolar disorder: a systematic review and meta-analysis

Abstract: The serotonin transporter (5-HTT) is a candidate gene for bipolar disorder (BPD). It has been investigated for association with the illness in a series of studies, but overall results have been inconsistent and its role in the disorder remains controversial. Systematic reviews using metaanalytical techniques are a useful method for objectively and reproducibly assessing individual studies and generating combined results. We performed two meta-analyses of published studies-both population-based and family-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
96
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(101 citation statements)
references
References 84 publications
2
96
0
3
Order By: Relevance
“…In another study performed among the Croatian population, authors reported that this allele was present in 1% of the healthy controls, and 2% of suicide victims. This allele seems to be rare in other European Caucasian populations (healthy controls) as well -English 3%, French and german 1%, Scottish 1%, Spanish 2% (Cho et al, 2005).…”
Section: Discussionmentioning
confidence: 89%
“…In another study performed among the Croatian population, authors reported that this allele was present in 1% of the healthy controls, and 2% of suicide victims. This allele seems to be rare in other European Caucasian populations (healthy controls) as well -English 3%, French and german 1%, Scottish 1%, Spanish 2% (Cho et al, 2005).…”
Section: Discussionmentioning
confidence: 89%
“…39,41,42,58 Clinical association studies have further examined the relationship between SERTLPR alleles and psychiatric disorders and anxiety-related personality traits, [59][60][61][62][63][64][65][66] suicide, 67,68 alcoholism, 69,70 response to antidepressants [71][72][73] and brain function as revealed by MRI scans. [74][75][76][77] Although many studies have reported correlations between SERTLPR alleles and SERT expression levels or clinical phenotype, almost an equal number of studies have not.…”
Section: Discussionmentioning
confidence: 99%
“…We integrated population-based and family-based association studies into a single meta-analysis using the method described in detail elsewhere (Cho et al, 2005;Kazeem and Farrall, 2005;Lohmueller et al, 2003). Briefly, counts of alleles in case and control groups in population-based studies were summarized in two-by-two tables.…”
Section: Statistical Analysesmentioning
confidence: 99%